Effort to Improve Overall Equipment Effectiveness Performance with Six Big Losses Analysis in the Packaging Industry PT BMJ - Fahriza Nurul Azizah; Dimas Nurwinata Rinaldi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
Increasing productivity is very important for companies to gain success in their business processes. This paper describes a case study of a manufacturing company that produces packaging products. PT BMJ is one of the companies engaged in the packaging industry. Low productivity and increased product demand for Offset machines becomes quite an important issue in the company, so that it becomes the objects of this research. Overall Equipment Effectiveness (OEE) is one of the methods that can measure machine effectiveness with three assessment factors, namely: availability, performance, and quality. Measurement of the OEE value and analysis of six big losses are carried out as an effort to increase the OEE value of machines and improve the production system in the company. The root cause of the problem is identified by using a causal diagram to be able to provide several suggestions for improvements. Based on the results comparison of OEE value before and after the implementation of improvement on the Offset machine, these improvements can increase the OEE value by 7.13% in two month implementation. Although the increase in OEE has not yet reached the criteria for World Class OEE, the proposed improvement has been able to reduce six big losses and increase the value of OEE.